Piezoelectric laminate and piezoelectric element

By using Ti and TiW as the first layer in the calcium-manganese oxide fuel cell electrode material and forming Ir with (111) plane inclination as the second layer thereon, the challenge of improving electrochemical performance and long-term reliability is solved, and efficient electrochemical performance and long-term stability is achieved.

JP7667052B2Active Publication Date: 2025-04-22FUJIFILM CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021157102
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-27
Publication Date
2025-04-22
Estimated Expiration
2041-09-27

AI Technical Summary

Technical Problem

The prior art present challenges in improving the electrochemical performance and long-term reliability of calcium-manganese oxide fuel cells, especially by maintaining high electrochemical performance while increasing manufacturing process complexity and cost.

Method used

By introducing titanium (Ti) and titanium tungsten (TiW) as the main components into the electrode material, and forming an iridium dioxide (Ir) with a high impurity with a (111) plane inclination as the second layer on the calcium-manganese oxide, thereby reducing the grain size of iridium dioxide and reducing the formation of the dielectric phase.

Benefits of technology

It is achieved to improve the electrochemical performance and long-term reliability of calcium-manganese oxide fuel cells without increasing the complexity and cost of the manufacturing process, reduce the formation of the dielectric phase, and improve the stability and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667052000002
    Figure 0007667052000002
  • Figure 0007667052000003
    Figure 0007667052000003
  • Figure 0007667052000004
    Figure 0007667052000004
Patent Text Reader

Abstract

To provide a piezoelectric laminate and a piezoelectric element capable of improving piezoelectric characteristics and drive stability without increasing process load.SOLUTION: A piezoelectric laminate and a piezoelectric element comprise on a substrate a lower electrode layer, a piezoelectric film containing perovskite type oxide, and an upper electrode layer in this order. The lower electrode layer includes: a first layer arranged in contact with the substrate; and a second layer arranged in contact with the piezoelectric film. The first layer contains Ti or TiW as a main component. The second layer contains Ir as a main component and is a uniaxial orientation film oriented to a (111) plane. The half width at half maximum of an X-ray diffraction peak from the (111) plane is 0.3° or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a piezoelectric laminate and a piezoelectric element. [Background technology]

[0002] Perovskite oxides such as lead zirconate titanate (Pb(Zr,Ti)O3, hereafter referred to as PZT) are known as materials with excellent piezoelectric and ferroelectric properties. Piezoelectrics made of perovskite oxides are used as piezoelectric films in piezoelectric elements that have a lower electrode, a piezoelectric film, and an upper electrode on a substrate. These piezoelectric elements are being deployed in a variety of devices, including memories, inkjet heads (actuators), micromirror devices, angular velocity sensors, gyro sensors, ultrasonic elements (PMUT: Piezoelectric Micromachined Ultrasonic Transducers), and vibration power generation devices.

[0003] When applying piezoelectric elements to devices, it is desirable for the piezoelectric elements to have high piezoelectric properties because higher piezoelectric properties lead to lower power consumption. To date, methods have been considered to improve the piezoelectric properties, such as improving the crystallinity of the piezoelectric film or reducing the resistance of the electrode layer.

[0004] As the lower electrode layer of a piezoelectric element, an Ir layer is often used from the viewpoints of adhesion to the piezoelectric film and low resistance. In order to reduce resistance, the Ir layer is generally made to have a thickness of 150 nm or more. Although the Ir layer has good adhesion to the piezoelectric film, it does not have good adhesion to the silicon substrate, so an adhesion layer made of a TiW layer or a Ti layer is often provided between the Ir layer and the substrate (Patent Documents 1 and 2).

[0005] Patent Document 3 proposes a laminated structure in which an Ir layer and an Au layer are laminated in order to further reduce the resistance of the lower electrode layer. By using Au, which has a higher conductivity than Ir, it is possible to achieve low resistance in the entire lower electrode layer.

[0006] On the other hand, when a piezoelectric film mainly composed of perovskite oxide is formed on an Ir layer, there is a problem that a different phase, pyrochlore phase, is easily generated at the interface with the lower electrode layer. Since the pyrochlore phase is a paraelectric, its formation causes a decrease in the dielectric constant and deterioration of the piezoelectric properties. Furthermore, piezoelectric elements that contain the pyrochlore phase at the interface between the piezoelectric film and the lower electrode layer are more susceptible to peeling and have lower long-term reliability than piezoelectric elements in which the pyrochlore phase is suppressed.

[0007] Patent Document 4 proposes providing an orientation control layer (seed layer) on the lower electrode layer as a method for suppressing the formation of the pyrochlore phase and improving the crystallinity of the piezoelectric film. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2016 / 051644 [Patent Document 2] JP 2009-70955 A [Patent Document 3] JP 2010-056426 A [Patent Document 4] JP 2018-82052 A Summary of the Invention [Problem to be solved by the invention]

[0009] The lower electrode materials (specifically, Ir and Ti or TiW) disclosed in Patent Documents 1 and 2 and currently widely used in actual devices are materials narrowed down based on past performance. The conventionally used lower electrode materials have good interfacial reactions with the piezoelectric body and are superior in long-term durability (stability) compared to other materials, so there is a strong demand to avoid changing these lower electrode materials. On the other hand, there is also a demand for further improvement in the long-term reliability of piezoelectric elements.

[0010] As in Patent Document 3, low resistance can be achieved by providing an Au layer on the lower electrode layer. On the other hand, it has been found that when the lower electrode layer has an Au layer, the long-term reliability is lower than in the case of the laminated structure of an Ir layer and a TiW or Ti adhesion layer disclosed in Patent Documents 1 and 2. This is thought to be due to the diffusion of Au caused by the high temperature of film formation when sputtering the piezoelectric film on the lower electrode layer. It is speculated that Au has a relatively low melting point and diffuses into the piezoelectric film during film formation, making it more likely to cause leaks.

[0011] In Patent Document 4, an orientation control layer is provided to improve the crystallinity of the piezoelectric film, thereby improving the piezoelectric characteristics and long-term stability. However, since a new layer called an orientation control layer is introduced in addition to the piezoelectric film and electrodes, there is a problem that the load on the manufacturing process is large.

[0012] The technology disclosed herein has been made in consideration of the above circumstances, and has an object to provide a piezoelectric laminate and a piezoelectric element having improved piezoelectric characteristics and drive stability without increasing the process load. [Means for solving the problem]

[0013] Specific means for solving the above problems include the following aspects.

[0014] The piezoelectric laminate of the present disclosure is a piezoelectric laminate including, in this order, a lower electrode layer, a piezoelectric film including a perovskite oxide, and an upper electrode layer on a substrate, the lower electrode layer includes a first layer disposed in contact with the substrate and a second layer disposed in contact with the piezoelectric film; The first layer is mainly composed of Ti or TiW. The second layer is a uniaxially oriented film containing Ir as a main component and oriented in the (111) plane, with the half-width at half maximum of the X-ray diffraction peak from the (111) plane being 0.3° or more.

[0015] In the piezoelectric laminate of the present disclosure, the half width at half maximum of the X-ray diffraction peak from the (111) plane is preferably 0.35° or more.

[0016] In the piezoelectric laminate of the present disclosure, the second layer preferably has an Ir (111) plane inclined at 1° or more with respect to the thickness direction.

[0017] In the piezoelectric laminate of the present disclosure, the second layer preferably has a thickness of 50 nm or less.

[0018] In the piezoelectric laminate of the present disclosure, the thickness of the lower electrode layer is preferably 200 nm or more.

[0019] In the piezoelectric laminate of the present disclosure, the sheet resistance of the lower electrode layer is preferably 1 Ω / □ or less.

[0020] In the piezoelectric laminate of the present disclosure, the height difference of the surface irregularities of the piezoelectric film is preferably 100 nm or less.

[0021] In the piezoelectric laminate of the present disclosure, the perovskite oxide preferably contains Pb, Zr, Ti and O.

[0022] In particular, the perovskite oxide is a compound represented by the following general formula (1): Pb{(Zr x Ti 1-x ) 1-y B1 y}O3(1) 0 <x<1、0<y<0.4、 B1 is preferably one or more elements selected from the group consisting of V, Nb, Ta, Sb, Mo and W.

[0023] In the piezoelectric laminate of the present disclosure, the piezoelectric film preferably has a columnar structure made up of a large number of columnar crystals.

[0024] In the piezoelectric laminate of the present disclosure, the (100) or (001) plane of the columnar crystals preferably has an inclination of 1° or more with respect to the surface of the substrate.

[0025] The piezoelectric element of the present disclosure comprises: and an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate. Effect of the Invention

[0026] According to the piezoelectric laminate and piezoelectric element of the present disclosure, it is possible to improve the piezoelectric characteristics and driving stability without increasing the process load. The method for producing the product is as follows: [Brief description of the drawings]

[0027] [Figure 1] 1 is a cross-sectional view showing a layer structure of a piezoelectric element according to an embodiment of the present invention. [Diagram 2] 4 is an explanatory diagram of the orientation state of the second layer (Ir layer) of the lower electrode layer in the present embodiment. FIG. [Diagram 3] 1 is an explanatory diagram of the orientation of an Ir layer used as a lower electrode layer in a conventional piezoelectric element. [Figure 4] FIG. 2 is an enlarged schematic view of a piezoelectric film. [Diagram 5] 1 is an XRD chart of Comparative Example 1. [Figure 6] 1 is an XRD chart of Example 1. [Figure 7] FIG. 2 is a diagram showing the Ir(111) peak of Comparative Example 1. [Figure 8] FIG. 2 is a diagram showing the Ir(111) peak of Example 1. [Figure 9] FIG. 2 is a diagram showing the Ir(111) rocking curve measurement data of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the thicknesses and ratios of each layer are appropriately changed for ease of viewing, and do not necessarily reflect the actual thicknesses and ratios.

[0029] "Piezoelectric laminate 5 and piezoelectric element 1 according to the first embodiment" Fig. 1 is a cross-sectional schematic diagram showing the layer structure of a piezoelectric stack 5 of the first embodiment and a piezoelectric element 1 including the piezoelectric stack 5. As shown in Fig. 1, the piezoelectric element 1 includes a piezoelectric stack 5 and an upper electrode layer 18. The piezoelectric stack 5 includes a substrate 10, and a lower electrode layer 12 and a piezoelectric film 15 including a perovskite oxide, which are stacked on the substrate 10. Here, "lower" and "upper" do not mean up and down in the vertical direction, but simply refer to the electrode disposed on the substrate 10 side across the piezoelectric film 15 as the lower electrode layer 12 and the electrode disposed on the opposite side of the piezoelectric film 15 to the substrate 10 as the upper electrode layer 18.

[0030] In the piezoelectric laminate 5 and piezoelectric element 1 of this embodiment, the lower electrode layer 12 includes a first layer 21 arranged in contact with the substrate 10, and a second layer 22 arranged in contact with the piezoelectric film 15. The first layer 22 is a layer mainly composed of Ti (titanium) or TiW (titanium-tungsten alloy). In this specification, the term "main component" refers to a component that accounts for 90 at% or more of the constituent elements. When TiW is the main component, the total of the Ti content and the W content may be 90 at% or more.

[0031] The second layer 22 is a layer containing Ir as a main component, and may be referred to as the Ir layer 22 below. The half-width at half maximum of the X-ray diffraction peak from the (111) plane of the Ir layer 22 (hereinafter referred to as the Ir(111) peak) is 0.3° or more. The half-width at half maximum of the Ir(111) peak is preferably 0.35° or more. The wider the half-width at half maximum of the Ir(111) peak, the lower the crystallinity, and the wider the half-width, the more the pyrochlore phase tends to be suppressed. On the other hand, in order to further lower the crystallinity of the Ir layer 22, a treatment such as adding an impurity element is required, and there is a concern that the addition of the impurity element may lower the adhesion with the piezoelectric film. Currently, the half-width of the Ir(111) peak is preferably 0.45° or less, more preferably 0.4° or less.

[0032] Here, the half-width at half maximum of the Ir(111) peak is measured as follows. The upper electrode layer 18 of the piezoelectric element is removed, and an XRD chart is obtained by thin-film XRD (X-ray diffraction) diffraction in a state in which the lower electrode layer 12 and the piezoelectric film 15 are provided on the substrate 10. A predetermined function is fitted to the Ir(111) peak in the XRD chart. The Ir(111) peak appears near 2θ=40.7°. The half-width at half maximum is calculated as the distance between the 2θ value showing the maximum value of the peak shown by the fitting curve and the 2θ value that is half the maximum value and does not overlap with other peaks (see FIG. 8).

[0033] When Ir is deposited on a substrate by sputtering, a naturally oriented film is formed with preferential orientation in the (111) plane. Crystallinity is related to the half-width at half maximum of the Ir(111) peak in the XRD chart (see FIG. 8) obtained by XRD diffraction. The wider the half-width at half maximum of Ir(111), the lower the crystallinity, and the narrower the half-width at half maximum, the higher the crystallinity. A half-width at half maximum of 0.3° or more indicates that there is a disturbance in the orientation of the (111) plane of the Ir layer 22, and the crystallinity is somewhat low.

[0034] In this embodiment, the (111) plane of the Ir layer 22 is inclined at 1° or more with respect to the thickness direction.

[0035] FIG. 2 is a schematic diagram of the Ir layer 22 of this embodiment, and the particles 22a in the diagram represent Ir elements. As shown in FIG. 2, the inclination of the (111) plane to the thickness direction of 1° or more means that the inclination α of the direction perpendicular to the (111) plane

[0111] to the thickness direction N is 1° or more. Here, the thickness direction N is the thickness direction of the Ir layer, and is a direction perpendicular to the surface 10a of the substrate 10. The actual Ir layer 22 contains many crystals, and the inclination direction of the (111) plane of each crystal varies. In this specification, the inclination α of the (111) plane in the Ir layer 22 is defined as a value measured by rocking curve measurement by X-ray diffraction. Specifically, the inclination α of the (111) plane is calculated from the split width of the (111) diffraction peak in the rocking curve measurement data (see Examples).

[0036] The (111) plane is the preferred orientation plane of Ir, and conventionally, an Ir layer oriented so that the (111) plane is perpendicular to the thickness direction, i.e., the

[0111] direction coincides with the thickness direction N, as shown in Fig. 3, has been used as the lower electrode layer. When a piezoelectric film made of a perovskite oxide is formed on a highly crystalline Ir layer as shown in Fig. 3, a pyrochlore phase is likely to form in the early stages of film formation. In response to this, the present inventors have found that the growth of the pyrochlore phase can be suppressed by reducing the crystallinity of the Ir layer 22 (see Examples).

[0037] The Ir(111) plane preferably has an inclination α of 1° or more and 15° or less with respect to the thickness direction N, and more preferably has an inclination of 1° or more and 8° or less.

[0038] In addition, the greater the inclination α of the (111) plane in the first layer 21 with respect to the thickness direction N, the greater the effect of suppressing the growth of the pyrochlore phase, and this is preferable. On the other hand, by setting the inclination to 15° or less, it is possible to suppress the dominance of other oriented planes, which is also preferable.

[0039] The thickness t2 of the second layer 22, i.e., the Ir layer 22, is preferably 50 nm or less. The thickness t2 is more preferably less than 50 nm, and further preferably 45 nm or less. From the viewpoint of being able to form a uniform film, the thickness t2 is preferably 10 nm or more.

[0040] The overall thickness t of the lower electrode layer 12 is preferably 200 nm or more, and more preferably 250 nm or more, and is preferably 500 nm or less, and more preferably 400 nm or less.

[0041] The thickness t of the lower electrode layer 12 and the thickness t2 of the Ir layer 22 can be estimated from a scanning electron microscope (SEM) image, a transmission electron microscope (TEM) image, or a secondary ion mass spectrometry (SIMS) analysis of the cross section of the piezoelectric element.

[0042] The sheet resistance of the lower electrode layer 12 is preferably 1 Ω / □ or less, and more preferably 0.8 Ω / □ or less. The sheet resistance can be measured by a four-probe method using a resistivity meter.

[0043] The piezoelectric film 15 contains a perovskite oxide represented by the general formula ABO3. In the general formula, A is an A-site element and is one or a combination of two or more of Pb, Ba (barium), La (lanthanum), Sr, Bi (bismuth), Li (lithium), Na (sodium), Ca (calcium), Cd (cadmium), Mg (magnesium), and K (potassium). In the general formula, B is a B-site element, and is one or a combination of two or more of Ti, Zr, V (vanadium), Nb (niobium), Ta (tantalum), Cr (chromium), Mo (molybdenum), W (tungsten), Mn (manganese), Fe (iron), Ru, Co (cobalt), Ir, Ni (nickel), Cu (copper), Zn (zinc), Ga (gallium), In, tin, antimony (Sb), and lanthanide elements. In the general formula, O is oxygen. The standard ratio of A:B:O is 1:1:3, but it may deviate within the range in which a perovskite structure can be obtained.

[0044] Preferably, the perovskite oxide accounts for 80 mol % or more, and more preferably, 90 mol % or more of the piezoelectric film 15. Furthermore, the piezoelectric film 15 is preferably made of a perovskite oxide (however, containing inevitable impurities).

[0045] The perovskite oxide is preferably a lead zirconate titanate (PZT) type oxide containing Pb (lead), Zr (zirconium), Ti (titanium) and O (oxygen).

[0046] In particular, the perovskite oxide is preferably a compound represented by the following general formula (1) which contains an additive B in the B site of PZT. Pb{(Zr x Ti 1-x ) 1-y B1 y}O3(1) Here, B1 is preferably one or more elements selected from V (vanadium), Nb (niobium), Ta (tantalum), Sb (antimony), Mo (molybdenum), and W (tungsten). Most preferably, B1 is Nb. Here, 0 < x < 1 and 0 < y < 0.4. In the general formula (1), Pb:{(Zr x Ti 1+x ) 1-y B y}:O is based on 1:1:3, but may deviate within the range where a perovskite structure can be obtained.

[0047] B1 may be a single element such as only V or only Nb, or a combination of two or more elements such as a mixture of V and Nb, or a mixture of V, Nb, and Ta. When B1 is these elements, a very high piezoelectric constant can be realized in combination with the Pb of the A-site element.

[0048] In addition, as shown in the cross-sectional schematic diagram of FIG. 4, the piezoelectric film 15 preferably has a columnar structure film including a large number of columnar crystals 17. The large number of columnar crystals 17 preferably extend non-parallel to the surface of the substrate 10 (see FIG. 1) and are a uniaxially oriented film with aligned crystal orientations. By adopting an oriented structure, a larger piezoelectric property can be obtained. The piezoelectric film 15 contains a pyrochlore phase 16 at the interface with the second layer 22 of the lower electrode layer 12. Details will be described later, but the pyrochlore phase 16 is in a sufficiently suppressed state. The pyrochlore phase 16 is preferably 20 nm or less. The pyrochlore phase 16 is not uniformly formed on the surface of the lower electrode layer 12, but grows partially as shown in FIG. 4. The calculation method of the thickness of the pyrochlore phase 16 will be described in the examples.

[0049] In the example shown in FIG. 4, the longitudinal direction of the columnar crystal has an inclination β of 1° or more with respect to the normal (thickness direction N) of the substrate. This means that the orientation plane of the piezoelectric film 15 has an inclination of 1° or more with respect to the surface of the substrate. Here, the orientation plane is the (100) plane or the (001) plane. Thus, in the piezoelectric film 15, it is preferable that the (100) plane or the (001) plane of the columnar crystal is inclined by 1° or more with respect to the surface of the substrate. In this example, the lattice constants of the a-axis and the c-axis in the perovskite structure are almost the same, and the (100) plane and the (001) plane cannot be distinguished by XRD analysis. However, it can be confirmed by XRD analysis that the film is oriented in at least one of the planes.

[0050] The thickness of the piezoelectric film 15 is usually 200 nm or more, for example, 0.2 μm to 5 μm, and preferably 1 μm or more.

[0051] The height difference of the surface unevenness of the piezoelectric film 15 is preferably 100 nm or less. A method for measuring the surface unevenness will be described in the Examples below, and the height difference of the surface unevenness is the maximum unevenness difference, i.e., peak to valley (PV value). Here, the period of the surface unevenness is not a minute period such as several tens of nm to several hundreds of nm, but a period on the order of μm.

[0052] The PV value of the surface unevenness of the piezoelectric film 15 is 100 nm or less, which can improve the pressure resistance and driving stability of the piezoelectric element. It is more preferable that the PV value of the surface unevenness of the piezoelectric film 15 is 80 nm or less.

[0053] The height difference of the surface unevenness can be measured in dynamic force mode (DFM) using a scanning probe microscope (SPM). When a patterned upper electrode layer 18 is formed on the piezoelectric film 15, the height difference of the surface unevenness can be measured on the exposed surface of the piezoelectric film 15 where the upper electrode layer 18 is not formed. Alternatively, it can be measured on the surface of the piezoelectric film 15 before the upper electrode layer 18 is formed.

[0054] The substrate 10 is not particularly limited, and examples thereof include substrates of silicon, glass, stainless steel, yttrium-stabilized zirconia, alumina, sapphire, silicon carbide, etc. The substrate 10 may be a laminated substrate such as a silicon substrate with a thermally oxidized film, in which a SiO2 oxide film is formed on the surface of a silicon substrate.

[0055] The upper electrode layer 18 is an electrode that is paired with the lower electrode layer 12 and is used to apply a voltage to the piezoelectric film 15. There are no particular limitations on the main component of the upper electrode layer 18, and examples of the main component include electrode materials that are generally used in semiconductor processes, as well as conductive oxides such as ITO (Indium Tin Oxide), LaNiO3, and SRO (SrRuO3), and combinations of these.

[0056] The thickness of the upper electrode layer 18 is not particularly limited, but is preferably about 50 nm to 300 nm, and more preferably 100 nm to 300 nm.

[0057] In the piezoelectric laminate 5 and the piezoelectric element 1 of this embodiment, the lower electrode layer 12 includes a first layer 21 arranged in contact with the substrate 10 and a second layer 22 arranged in contact with the piezoelectric film 15, the first layer 21 being mainly composed of Ti or TiW, and the second layer 22 being mainly composed of Ir. Ti and TiW have good adhesion to the substrate 10, and Ir has good adhesion to the piezoelectric film 15. Therefore, interlayer peeling is suppressed and long-term reliability is high. The lower electrode layer 12 may include another metal layer between the first layer 21 and the second layer 22. However, since Ir and TiW, or Ir and Ti, respectively, have high adhesion, it is most preferable that the lower electrode layer 12 has a two-layer structure of the first layer 21 and the second layer 22.

[0058] In the piezoelectric laminate 5 and the piezoelectric element 1 of this embodiment, the Ir layer 22, which is the second layer 22, is a uniaxially oriented film oriented in the Ir (111) plane, and the half-width at half maximum of the X-ray diffraction peak from the (111) plane of Ir is 0.3° or more. As described above, the half-width at half maximum of the X-ray diffraction peak is 0.3° or more, which means that the crystallinity of the Ir layer 22 is somewhat low and the Ir layer 22 is not sufficiently oriented to the (111) plane, which is the preferred orientation plane. If the Ir (111) plane is disturbed, the growth of the pyrochlore phase can be suppressed during the deposition of the piezoelectric film 15 containing a perovskite oxide provided on the upper layer. Since the pyrochlore phase can be sufficiently suppressed, the piezoelectric laminate 5 and the piezoelectric element 1 can be obtained that include a good piezoelectric film 15 containing a perovskite oxide. Since the piezoelectric film 15 includes a piezoelectric film in which the pyrochlore phase is suppressed, high piezoelectric characteristics can be obtained, and higher driving stability than before can be obtained.

[0059] Furthermore, the piezoelectric laminate 5 and piezoelectric element 1 of this embodiment are obtained by directly laminating piezoelectric films on the Ir layer 22 without providing a layer such as an orientation control layer, and therefore can be manufactured without increasing the process load as occurs in the case of a conventional orientation control layer, thereby suppressing increases in manufacturing costs.

[0060] Furthermore, if the half-width at half maximum of the X-ray diffraction peak from the Ir(111) plane of the Ir layer 22 is 0.35° or more, the effect of suppressing the growth of the pyrochlore phase can be further improved, and as a result, the piezoelectric characteristics and driving stability can be further improved.

[0061] When the half-width at half maximum of the X-ray diffraction peak from the Ir (111) plane is 0.45° or less, preferably 0.4° or less, the growth of the pyrochlore phase can be suppressed while maintaining the resistance value of the Ir layer 22 and its adhesion to the piezoelectric film 15 at the same levels as those of a highly crystalline Ir layer.

[0062] In the piezoelectric laminate 5 and piezoelectric element 1 of this embodiment, the Ir(111) plane of the second Ir layer 22 is inclined by 1° or more with respect to the thickness direction. This indicates that the orientation of the Ir(111) plane is disturbed, and the half-width at half maximum is 0.3° or more, and similarly indicates low crystallinity. The slightly reduced orientation of the Ir(111) plane also provides the effect of suppressing the pyrochlore phase.

[0063] In the piezoelectric laminate and the piezoelectric element 1 of this embodiment, the thickness t2 of the second layer 22 of the lower electrode layer 12, i.e., the Ir layer 22, is preferably 50 nm or less. By making the thickness t2 of the Ir layer 22 50 nm or less, the orientation of the Ir (111) plane can be reduced. The inventors have found that by making the thickness t2 of the Ir layer 22 75 nm or less, the half-width of the Ir (111) peak can be 0.30° or more, and by making the thickness t2 of the Ir layer 22 50 nm or less, thinner than the conventional one, the half-width of the Ir (111) peak can be 0.35° or more. The method of making the half-width of the Ir (111) peak 0.30° or more is not limited to the method of forming the Ir layer 22 thinner than the conventional one, and other methods such as reducing the crystallinity of the first layer 21 that is the underlayer of the Ir layer 22 can also be used. Furthermore, by making the Ir layer 22 50 nm or less, the amount of Ir used can be reduced compared to the conventional case, so that the material cost of the lower electrode layer 12 can be reduced, and the manufacturing cost can be reduced.

[0064] If the thickness t of the lower electrode layer 12 is 200 nm or more, sufficient conductivity can be obtained as the lower electrode layer 12. Furthermore, if the thickness t of the lower electrode layer 12 is 250 nm or more, even better conductivity can be obtained. By making the Ir layer 22 thinner than before, but making the first layer 22 somewhat thick, and making the entire lower electrode layer 12 200 nm or more, the sheet resistance can be reduced.

[0065] If the sheet resistance of the lower electrode layer 12 is 1 Ω / □ or less, it is suitable for pairing with the upper electrode layer 18 to apply a voltage to the piezoelectric film 15 .

[0066] The piezoelectric film 15 contains a perovskite oxide, and when the piezoelectric film 15 contains a perovskite oxide containing Pb, the Pb is easily removed, and the pyrochlore phase is easily formed in the early stage of film formation. Therefore, the effect of suppressing the pyrochlore phase is particularly high when the half width at half maximum of the X-ray diffraction peak from the Ir (111) plane is 0.3° or more. Among the perovskite oxides containing Pb, PZT-based perovskite oxides containing Pb, Zr, Ti, and O are particularly preferred because of their high piezoelectric properties. In particular, the perovskite oxide is a compound represented by the following general formula (1), Pb{(Zr x Ti 1-x ) 1-y B1 y}O3(1) 0 <x<1、0<y<0.4、 If B1 is one or more elements selected from the group consisting of V, Nb, Ta, Sb, Mo and W, even higher piezoelectric properties can be obtained.

[0067] The piezoelectric element 1 or the piezoelectric laminate 5 in each of the above-described embodiments is applicable to ultrasonic devices, mirror devices, sensors, memories, and the like. EXAMPLES

[0068] Specific examples and comparative examples of the piezoelectric element of the present disclosure will be described below. First, a method for producing the piezoelectric element of each example will be described. A radio frequency (RF) sputtering device was used to deposit each layer. Conditions other than the configuration of the lower electrode layer were the same for each example. The manufacturing method will be described with reference to the reference numerals of each layer of the piezoelectric element 1 shown in FIG. 1.

[0069] (Bottom electrode layer deposition) An 8-inch silicon substrate with a thermal oxide film was used as the substrate 10. The lower electrode layer 12 was formed on the substrate 10 by RF (radio-frequency) sputtering. Specifically, the lower electrode layer 12 was formed by stacking a TiW layer 21 as a first layer 21 and an Ir layer 22 as a second layer 22 in this order on the substrate 10. The thicknesses of the TiW layer 21 and the Ir layer 22 differed for each example and were as shown in Table 1. The sputtering conditions for each layer were as follows:

[0070] -TiW layer sputtering conditions- Target-substrate distance: 100mm Target input power: 600W Ar gas pressure: 0.5 Pa Substrate temperature setting: 350℃

[0071] -Ir layer sputtering conditions- Target-substrate distance: 100mm Target input power: 600W Ar gas pressure: 0.1 Pa Substrate temperature setting: 350℃

[0072] (Piezoelectric film deposition) The substrate 10 with the lower electrode layer 12 was placed in an RF sputtering device, and a Nb-doped PZT film with a B site doping amount of 12 at % was formed to a thickness of 2 μm as the piezoelectric film 15. The sputtering conditions at this time were as follows:

[0073] -Piezoelectric film sputtering conditions- Target-substrate distance: 60mm Target input power: 500W Degree of vacuum: 0.3 Pa, Ar / O2 mixed atmosphere (O2 volume fraction 2.0%) Substrate temperature setting: 700℃

[0074] (Top electrode layer formation) Next, the substrate 10 after the formation of the piezoelectric film 15 was placed in a deposition chamber of an RF sputtering device, and an ITO (Indium Tin Oxide) target was used to form an ITO layer having a thickness of 200 nm as the upper electrode layer 18. Before forming the upper electrode layer 18, a lift-off pattern for an evaluation sample was prepared on the piezoelectric film 15, and the upper electrode layer 18 was formed on the lift-off pattern. The deposition conditions for the upper electrode layer 18 were as follows:

[0075] -Upper electrode layer sputtering conditions- Target-substrate distance: 100mm Target input power: 200W Degree of vacuum: 0.3 Pa, Ar / O2 mixed gas (O2 volume fraction 5%) Substrate temperature setting: RT (room temperature)

[0076] (Formation of electrode pattern for evaluation) After the upper electrode layer 18 was formed, the upper electrode layer was lifted off along a lift-off pattern by a lift-off method, and the upper electrode layer 18 was patterned.

[0077] By the above steps, a piezoelectric laminate substrate of each example was fabricated, which had a lower electrode layer, a piezoelectric film, and a patterned upper electrode layer on a substrate.

[0078] (Preparation of evaluation samples) -Evaluation sample 1- A rectangular piece measuring 2 mm×25 mm was cut out from the piezoelectric laminate substrate to prepare a cantilever as evaluation sample 1.

[0079] -Evaluation sample 2- A 25 mm×25 mm portion having an upper electrode layer patterned into a circle with a diameter of 400 μm at the center of the surface of the piezoelectric film was cut out from the piezoelectric laminate substrate, and used as evaluation sample 2.

[0080] <Evaluation of piezoelectric properties> The piezoelectric properties of each example and comparative example were evaluated using the piezoelectric constant d 31 was measured. Piezoelectric constant d31 The measurement was performed by cutting the piezoelectric element prepared as above into a rectangular shape of 2 mm x 25 mm to prepare a cantilever, and following the method described in I. Kanno et. al. Sensor and Actuator A 107 (2003) 68., by grounding the lower electrode layer 12 and applying a sine wave voltage of -10 V ± 10 V to the upper electrode layer 18. The results are shown in Table 1.

[0081] <Evaluation of long-term reliability> A time dependent dielectric breakdown (TDDB) test was conducted to evaluate the long-term reliability of each of the examples and comparative examples. Using evaluation sample 2, the lower electrode layer 12 was grounded in an environment of 120° C., and a voltage of −40 V was applied to the upper electrode layer 18 to measure the time (hr) from the start of voltage application until dielectric breakdown occurred. The measurement results are shown in Table 1. The TDDB test was conducted for 1000 hours, and those that did not experience dielectric breakdown up to 1000 hours are listed as 1000 in Table 1.

[0082] <Resistance value evaluation> Using a low resistivity meter Loresta AX, a dedicated four-point probe was used to measure the resistivity (sheet resistance) of the lower electrode layer 12. For each example, the resistivity was measured at the time when the lower electrode layer 12 was formed on the substrate 10.

[0083] <Crystallization> The crystallinity of the piezoelectric film (PZT film) and the Ir layer of the lower electrode layer of the piezoelectric laminate of each example was evaluated by XRD analysis using RINT-ULTIMA III manufactured by RIGAKU.

[0084] (Evaluation of peak intensity due to pyrochlore phase) Fig. 5 shows an XRD chart for Comparative Example 1, and Fig. 6 shows an XRD chart for Example 1. The crystallinity evaluation was carried out using the piezoelectric laminate before the formation of the upper electrode layer. The intensity of the heterogeneous pyrochlore phase (222) was determined from the XRD chart obtained for each example. The region where the pyrochlore phase (222) was detected was around 29°, and the peak intensity derived from the pyrochlore phase (222) was determined by removing background noise from the obtained XRD diffraction intensity (counts). Also, from the XRD chart, py(222) / {pr(100)+pr(110)+pr(111)}×100% was calculated as the pyrochlore ratio.

[0085] The strength from each side was determined as follows. The average number of counts at 2θ of 25° to 28° was taken as background noise N. The intensity of py(222) was determined by dividing N by the maximum number of counts in the range of 2θ from 28° to 30°. The pr(100) intensity was determined by dividing N by the maximum number of counts in the range of 2θ from 21° to 23°. The intensity of pr(110) was determined by dividing N by the maximum number of counts in the range of 2θ from 30° to 32°. The intensity of pr(111) was determined by dividing N by the maximum number of counts in the range of 2θ from 37.5° to 39.5°.

[0086] In FIG. 5 and FIG. 6, the peak values ​​of the perovskite phase (100) are equivalent. On the other hand, differences are observed in the pyrochlore phase (222). As shown in FIG. 5, in Comparative Example 1, there is a clear peak of the pyrochlore phase (222) at around 29°. In Example 1 shown in FIG. 6, the peak value of the pyrochlore phase (222) is lower than that of Comparative Example 1. As shown in FIG. 6, in Example 1, a PZT film uniaxially oriented in (001) was obtained. In each of Examples 2 to 4, a PZT film uniaxially oriented in (001) similar to that in Example 1 was obtained.

[0087] (FWHM of Ir(111) peak) From the XRD chart obtained for each example, the half width at half maximum of the Ir(111) peak was obtained. The Ir(111) peak occurs near 40.7°. FIG. 7 is an enlarged view of the vicinity of Ir(111) in the XRD chart of Comparative Example 1, and FIG. 8 is an enlarged view of the vicinity of Ir(111) in the XRD chart of Example 1. Ir(111) occurs near 2θ=40.7°. In Example 1 shown in FIG. 8, the peak overlaps with the peak of the TiW layer, which is the first layer of the lower electrode layer, because the peak is close to it. In Comparative Example 1, the peak of the TiW layer was hardly observed. Fitting was performed on the peak using a double Gaussian function. In the fitting curve of the Ir(111) peak, the width between the 2θ value showing the Ir(111) peak maximum value Ip and the 2θ value showing 1 / 2 the intensity of the maximum value Ip was obtained as the half width at half maximum (HWHM). The results are shown in Table 1.

[0088] <Tilt of the Ir(111) surface of the lower electrode layer from the substrate surface> For the examples and comparative examples, the crystallinity of the first layer was evaluated by XRD using a RINT-ULTIMAIII manufactured by RIGAKU, using samples before the upper electrode layer was formed. Specifically, the tilt of the (111) plane was obtained by measuring the deviation of the peak of the Ir (111) plane from the Ir peak position when the (111) plane is not tilted, using a rocking curve measurement. Figure 9 shows rocking curve measurement data for Example 1. The reference position shown in the figure is the peak position of the (111) plane that occurs when the (111) plane is parallel to the surface of the substrate. In the example shown in Figure 9, there is a first peak P1 and a second peak P2, and the split width is 10°. The center of the split width of the first peak P1 and the second peak P2 is the reference position, which means that in this example, the (111) plane of the first layer is tilted by 5° with respect to the state parallel to the substrate. The measured values ​​for each example are shown in Table 1.

[0089] <Pyrochlore phase thickness evaluation> For the examples and comparative examples, TEM (Transmission Electron Microscope) images were taken, and the thickness of the pyrochlore phase was determined from the TEM images. Since the contrast in the TEM images of the pyrochlore phase and the perovskite phase in the piezoelectric film is different, the region of the pyrochlore phase can be identified and the thickness can be calculated. It was observed that columnar crystals of perovskite-type oxide were formed in the parts of the piezoelectric film other than the pyrochlore phase. The thickness of the pyrochlore phase was calculated as the average thickness because the pyrochlore phase was not uniformly formed on the surface of the lower electrode layer.

[0090] Specifically, the original image is binarized at a predetermined threshold value using the contrast adjustment function of the image processing software, and the pyrochlore phase is extracted using the edge extraction function of the image processing software. The threshold value in this case is set so that noise is removed as much as possible and only those that can be clearly identified as pyrochlore phase are extracted. If the outline of the pyrochlore-type oxide layer is unclear in the binarized image, a contour line is empirically drawn while looking at the binarized image and the inside is filled in. The area of ​​the extracted pyrochlore phase is calculated from the number of pixels of the image processing software and divided by the field width of the TEM image to obtain the average layer thickness. Photoshop (registered trademark) was used as the image processing software here. The thickness of the pyrochlore phase obtained as described above is shown in Table 1.

[0091] <Measurement of surface irregularities of piezoelectric film> The surface unevenness was measured in dynamic force mode (DFM) using an S-image type scanning probe microscope (SPM: Scanning Probe Microscope) manufactured by Hitachi High-Tech Science Corporation. The surface unevenness was measured on the 5 μm 2 The maximum difference in surface unevenness, that is, peak to valley (PV value), was about 80 mm in all cases, and there was almost no difference between all the comparative examples and examples.

[0092] [Table 1]

[0093] As shown in Table 1, in the case of Examples 1 to 5 where the half width at half maximum of the Ir(111) peak is 0.3° or more, the pyrochlore phase is suppressed compared to Comparative Examples 1 and 2 where the half width at half maximum is less than 0.3°, and the result shows that the piezoelectric properties and long-term reliability are high. In particular, the effect of improving the long-term reliability was remarkable. By setting the thickness of the Ir layer to 75 nm, the half width at half maximum of the Ir(111) peak could be set to 0.3° or more, and by setting the thickness of the Ir layer to 50 nm or less, the half width at half maximum of the Ir(111) peak could be set to 0.35° or more. There was a tendency that the half width at half maximum of the Ir(111) peak could be increased as the Ir layer was made thinner. In addition, the larger the Ir(111) peak, the smaller the thickness of the pyrochlore phase could be, and the piezoelectric constant could be increased. Furthermore, from Examples 1 to 5, it was found that if the thickness of the lower electrode layer is 200 nm or more, the sheet resistivity of the lower electrode layer can be suppressed to 1 Ω / □ or less even if the Ir layer is suppressed to 50 nm or less. [Explanation of symbols]

[0094] 1 Piezoelectric element 10 Substrate 12 Lower electrode layer 15 Piezoelectric film 16 Pyrochlore phase 17 Columnar crystals 18 Upper electrode layer 21 1st layer 22 2nd layer (Ir layer) 22a Ir element

Claims

1. A piezoelectric laminate including a lower electrode layer and a piezoelectric film including a perovskite oxide, in this order, on a substrate, the lower electrode layer includes a first layer disposed in contact with the substrate and a second layer disposed in contact with the piezoelectric film; The first layer is mainly composed of Ti or TiW, the second layer is a uniaxially oriented film containing Ir as a main component and oriented in the (111) plane, and the half width at half maximum of the X-ray diffraction peak from the (111) plane is 0.3° or more and 0.45° or less.

2. 2. The piezoelectric stack according to claim 1, wherein the half width at half maximum of the X-ray diffraction peak from the (111) plane is 0.35° or more.

3. 3. The piezoelectric stack according to claim 1, wherein the (111) plane of the second layer is inclined at 1 degree or more with respect to a thickness direction.

4. The piezoelectric laminate according to claim 1 , wherein the second layer has a thickness of 50 nm or less.

5. The piezoelectric stack according to claim 4 , wherein the lower electrode layer has a thickness of 200 nm or more.

6. 6. The piezoelectric stack according to claim 1, wherein the lower electrode layer has a sheet resistance of 1 Ω / □ or less.

7. 7. The piezoelectric stack according to claim 1, wherein the height difference of the surface irregularities of the piezoelectric film is 100 nm or less.

8. The piezoelectric stack according to claim 1 , wherein the perovskite oxide contains Pb, Zr, Ti and O.

9. The perovskite oxide is a compound represented by the following general formula (1): ____________________ x () 1-x ))-. y ッ 3 () 0<x<1, 0<y<0.4, 9. The piezoelectric laminate according to claim 8, wherein B1 is one or more elements selected from the group consisting of V, Nb, Ta, Sb, Mo and W.

10. The piezoelectric laminate according to claim 1 , wherein the piezoelectric film has a columnar structure made up of a large number of columnar crystals.

11. 11. The piezoelectric stack according to claim 10, wherein the (100) or (001) plane of the columnar crystal has an inclination of 1° or more with respect to the surface of the substrate.

12. A piezoelectric laminate according to any one of claims 1 to 11, and an upper electrode layer provided on the piezoelectric film of the piezoelectric laminate.

Citation Information

Patent Citations

  • Ferroelectric capacitor and method of forming the ferroelectric capacitor

    JP2004006593A

  • Semiconductor device and method for manufacturing the same

    JP2004153019A

  • Dielectric element, piezoelectric element, ink-jet head, and manufacturing method therefor

    JP2005223318A

  • Semiconductor device, method of manufacturing the same, and thin-film device

    JP2007081378A

  • Piezoelectric device, ink-jet head using the same, and manufacturing method of piezoelectric device

    JP2009070955A